Metastable argon atom density in complex argon/acetylene plasmas determined by means of optical absorption and emission spectroscopy. (20th September 2016) - Sushkov, Vladimir; Herrendorf, Ann-Pierra; Hippler, Rainer
Abstract: Optical emission and absorption spectroscopy has been utilized to investigate the instability of acetylene-containing dusty plasmas induced by growing nano-particles. The density of Ar(1s5 ) metastable atoms was derived by two methods: tunable diode laser absorption spectroscopy and with the help of the branching ratio method of emitted spectral lines. Results of the two techniques agree well with each other. The density of Ar(1s3 ) metastable atoms was also measured by means of optical emission spectroscopy. The observed growth instability leads to pronounced temporal variations of the metastable and other excited state densities. An analysis of optical line ratios provides evidence for a depletion of free electrons during the growth cycle but no indication for electron temperature variations.